The importance and allocation of risks in Malaysia construction project - Wong, Ming Yien, 1986-; Khairulzan Yahya, supervisor; Fakulti Kejuruteraan Awam (2011)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2011